2008
DOI: 10.1088/0957-4484/19/38/384002
|View full text |Cite
|
Sign up to set email alerts
|

A new detection system for extremely small vertically mounted cantilevers

Abstract: Detection techniques currently used in scanning force microscopy impose limitations on the geometrical dimensions of the probes and, as a consequence, on their force sensitivity and temporal response. A new technique, based on scattered evanescent electromagnetic waves (SEW), is presented here that can detect the displacement of the extreme end of a vertically mounted cantilever. The resolution of this method is tested using different cantilever sizes and a theoretical model is developed to maximize the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
1
48
0
Order By: Relevance
“…4) with its spring constant (0.67 mN/m), we determine its force noise to be 1.9 f N/ √ Hz. Currently, the best custom cantilevers we are aware of have force noises of 23-29f N/ √ Hz in water [1,16,17] and commercial cantilevers have force-noises of 50-200 f N/ √ Hz [18]. We have shown that nanowires directionally scatter sufficient light to provide position detection with high sensitivity and bandwidth, without the need for an interferometric optical pathway.…”
Section: Figmentioning
confidence: 99%
“…4) with its spring constant (0.67 mN/m), we determine its force noise to be 1.9 f N/ √ Hz. Currently, the best custom cantilevers we are aware of have force noises of 23-29f N/ √ Hz in water [1,16,17] and commercial cantilevers have force-noises of 50-200 f N/ √ Hz [18]. We have shown that nanowires directionally scatter sufficient light to provide position detection with high sensitivity and bandwidth, without the need for an interferometric optical pathway.…”
Section: Figmentioning
confidence: 99%
“…The interaction with the water molecules results in the cantilever vibration being damped and the amplitude of vibration being decreased. The change in vibration of the probe is measured by a laser optical detection system, which is set beneath the thin quartz plate underneath the specimen (Antognozzi et al, 2008). Thus, when the specimen is moved in the x-y plane, the specimen topography can be measured by the probe at any particular position by keeping the vibration amplitude of the cantilever constant.…”
Section: Introduction To Bristol's Transverse Dynamic Force Microscopementioning
confidence: 99%
“…However, the majority of atomic force microscopy experiments are performed in air, and the tapping-mode detection speed of current highspeed cantilevers is an order of magnitude lower in air than in liquids. Traditional approaches to increasing the imaging rate of atomic force microscopy have involved reducing the size of the cantilever 4,5 , but further reductions in size will require a fundamental change in the detection method of the microscope [6][7][8] . Here, we show that high-speed imaging in air can instead be achieved by changing the cantilever material.…”
mentioning
confidence: 99%
“…A further size reduction would require fundamentally different detection techniques. Techniques such as near-field scattering and thin-metal-film piezoresistive sensing have been proposed [6][7][8] . However, such small cantilevers suffer from challenges in their implementation and are limited to use on very flat samples because of the minimal chipsample clearance.…”
mentioning
confidence: 99%